PENGARUH PENERAPAN METODE PEMBELAJARAN SOCRATES TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII SMP - Buang Saryantono; Partono (Epsilon: Jurnal Pendidikan Matematika, 2019)
The purpose of this research is to know the influence of a method of learning socrates on ability problem solving mathematical at grade student viii even junior high school number 9 Bandar Lampung. This research uses experimental methods with a population of all students class viii the junior high schools number 9 Bandar Lampung. Sampel consisting of two classes, class vii A as a class experiment in a learning of socrates were 34 students and students class viii C as a class control in a learning conventional were 34 students. A sample taken using techniques clusters random sampling. The ability of problem solving students using tests essays about 5 who first tested validity and reliability. The testing of hypotheses use t test it uses to research . Based on the results obtained analysis using t-tes formulas, t-hit = 6,39 and t on distribution of the significant level 5% is 2,00. It can be known if t-hit > t-daf so Ho rejected, means Ha accepted, So can be concluded is the influence of a method of learning of socrates the ability of problem solving mathematical students VIII the first half odd junior high schools 9 bandar lampung years lessons 2018 / 2019.